Family religiosity and climate: the protective role of personal interiorized religiosity in deviance propensity among justice-involved juveniles - Saladino, Valeria; Mosca, Oriana; Cabras, Cristina; Verrastro, Valeria; Lauriola, Marco (Frontiers in Psychology, 2024)
According to the literature, religious commitment could be a protective factor against dangerous behaviors, such as criminal offending, unsafe sex, and substance use. Our study aims to investigate the influence of family religiosity and climate on anger dysregulation and deviance propensity in a sample of 214 justice-involved boys from Italian Youth Detention Centers (range 14-25). The sample was divided into religious (n=102) and non-religious (n=112) justice-involved juveniles. Participants filled in the following questionnaires: Deviant Behavior Questionnaire, Aggression Questionnaire, Family Communication Scale, Moral Disengagement Scale, and the Multidimensional Scale of Perceived Social Support. We used a partial least square structural equation modeling (PLS_SEM) method to build our model and we found that Family Religiosity was positively associated with Family Climate which was negatively associated with Anger Dysregulation and Deviance Propensity, and Anger Dysregulation was positively related to Deviance Propensity. The multigroup analysis confirmed that for justice-involved juveniles who interiorized religious discipline and beliefs, Family Religiosity showed a positive association with Family Climate, which had a negative relationship with Anger Dysregulation, which strongly predicted Deviance Propensity. This result could be useful to promote new development goals and preventive activities and interventions based on positive religiosity values in juveniles' behavior.